Peningkatan Literasi Teknologi Rotary Kiln Electric Furnace dalam Mendukung Industri Nikel Sulawesi Tenggara - Irwan Syahib, Muhammad; Idris Putra , Muhammad; Indra, Indra; Setiawan , Adhi; Yuliana, Anita; Hadistio , Ryan Rinaldi; Putra Singarimbun , Aldo Putra; . Rahman , Muhammad Iqbal A. A; Rahman, La (FAKULTAS TEKNIK UMKENDARI, 2025)
Southeast Sulawesi is one of the largest nickel-producing centers in Indonesia, marked by the booming development of nickel processing industries (smelters) utilizing the Rotary Kiln Electric Furnace technology. This technology serves as the backbone of lateritic nickel refinement. However, access for Mechanical Engineering students to Rotary Kiln Electric Furnace technology for internship and research purposes is very limited, creating a gap between the academic curriculum and industry needs. This community service activity aims to bridge this gap through a scientific seminar that introduces the Rotary Kiln Electric Furnace working principles, key components relevant to Mechanical Engineering, and the available job descriptions in smelters. The implementation method includes interactive material delivery and in-depth discussions. The results of the activity show an increase in students' understanding of the Rotary Kiln Electric Furnace nickel processing cycle and the identification of the crucial role of Mechanical Engineering in the operation and maintenance of the Rotary Kiln, electric furnace, and supporting utility systems. The benefit gained is that students are equipped with foundational knowledge of Southeast Sulawesi's leading nickel technology, enhancing their readiness to compete in the job market within the smelter industry.